Study about the appropriate number of participants in map user studies - Bergmann Martins, Vinicius; Rosa Amorim, Fabrício; Augusto Reolon Schmidt, Marcio; Stamato Delazari, Luciene (International journal of cartography, 2023)
The minimum and the adequate number of participants in experiments with maps can vary significantly according to the characteristics of the participants, the maps, and especially the test's purpose. In this sense, the estimation of the adequate number of participants employed in carrying out tests involving map users bases the problem of this research. The study's hypothesis presupposes that it is possible to establish the number of participants for each group of methods of experiments with similar characteristics that group the tests. To this end, to compare terms found in the Web of Science database with those informed in the title, abstract, introduction, and methodology of 200 scientific articles published in the area of cartography, whose subject is related to map users, the research performed an analytical review of the works. As a result, the analysis made it possible to select 85 publications, such as adequacy to the subject of study, according to the methods used. The results obtained from the research make it possible to define the number of participants according to the purpose of the applied test when evaluating maps.